Impact of a Nationwide Training Program in Minimally Invasive Distal Pancreatectomy (LAELAPS). Issue 5 (November 2016) - de Rooij, Thijs; van Hilst, Jony; Boerma, Djamila; Bonsing, Bert A.; Daams, Freek; van Dam, Ronald M.; Dijkgraaf, Marcel G.; van Eijck, Casper H.; Festen, Sebastiaan; Gerhards, Michael F.; Koerkamp, Bas Groot; van der Harst, Erwin; et al.
Abstract : Objective: To study the feasibility and impact of a nationwide training program in minimally invasive distal pancreatectomy (MIDP). Summary of Background Data: Superior outcomes of MIDP compared with open distal pancreatectomy have been reported. In the Netherlands (2005 to 2013) only 10% of distal pancreatectomies were in a minimally invasive fashion and 85% of surgeons welcomed MIDP training. The feasibility and impact of a nationwide training program is unknown. Methods: From 2014 to 2015, 32 pancreatic surgeons from 17 centers participated in a nationwide training program in MIDP, including detailed technique description, video training, and proctoring on-site. Outcomes of MIDP before training (2005–2013) were compared with outcomes after training (2014–2015). Results: In total, 201 patients were included; 71 underwent MIDP in 9 years before training versus 130 in 22 months after training (7-fold increase, P < 0.001). The conversion rate (38% [n = 27] vs 8% [n = 11], P < 0.001) and blood loss were lower after training and more pancreatic adenocarcinomas were resected (7 [10%] vs 28 [22%], P = 0.03), with comparable R0-resection rates (4/7 [57%] vs 19/28 [68%], P = 0.67). Clavien-Dindo score ≥III complications (15 [21%] vs 19 [15%], P = 0.24) and pancreatic fistulas (20 [28%] vs 41 [32%], P = 0.62) were not significantly different. Length of hospital stay was shorter after training (9 [7–12] vs 7 [5–8] days, P < 0.001). Thirty-day mortality was 3% vs 0% ( P = 0.12). Conclusion: A nationwide MIDP training program was feasible and followed by a steep increase in the use of MIDP, also in patients with pancreatic cancer, and decreased conversion rates. Future studies should determine whether such a training program is applicable in other settings.